Globalization of Regulatory affairs in Healthcare Industry - MITTAL, NEETI; KULSHRESHTHA, VRINDA; DANG, SHWETA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Globalization is a term that defines exchange of goods and services between the countries which has a positive impact on economic transactions across national borders. Healthcare services are also influenced by globalization. Every country has its own regulatory agency which is responsible for its public health, health care systems, and financial resources. As the demand for safe food and medical products is increasing, the responsibility of the regulatory agencies is also increasing. They ensure the purity and efficacy of the medical products to protect their citizens. The paper will discuss globalization from the point of view of Food and Drug Administration, European Medicines Agency, Pharmaceuticals and Medical Devices Agency, and Central Drugs Standard Control Organization and will also discuss the impact of globalization on developing countries such as India, China, Brazil, and South Africa. The paper will also deal with the importance of the International Conference on Harmonization which has played a key role in bringing different regulatory agencies of the world to achieve the common goal of promoting globalization in healthcare. Keywords: ???